Lifetime trauma, symptoms of psychological disturbance, and suicidal ideation among university students in Malaysia - Siti Raudzah, Ghazali; Chen, Yoke Yong; Mardiana, Mohamad; Lee, Ping Yein; Zul Azlin, Razali; Noraskin, Pauzi; Alia Fadaliana, Majani (Springer Nature, 2023)
In many countries, mental disorders are high among university students. We conducted a cross-sectional research design among 1767 university students (71.2% were females and the remaining were males) who attended public universities in Sarawak. Questionnaires related to a history of lifetime trauma, posttraumatic stress disorder (PTSD), and depressive symptoms together with suicide behavior were surveyed. Results showed that at least 87% of students had lifetime trauma once, 9.6% exhibited PTSD symptoms, 15.5% exhibited depressive symptoms, and 12.9% of participants reported having suicidal behavior. There were significantly more females who reported having suicidal behaviors than males. Ethnicity was significantly associated with PTSD symptoms. PTSD and depressive symptoms were significant predictors of suicidal behavior. Other significant predictors for suicide behavior among those who were traumatized were near drowning, sexual assault, losing a family member, neglect, and bullying. This study provides a significant understanding of the link between PTSD, depressive symptoms, and suicidal behavior among Malaysian university students.